2000
DOI: 10.1021/ja002833v
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Abstracts a Nitrogen Atom from an Osmium Nitrido Complex To Give Nitrous Oxide

Abstract: The chemistry of nitric oxide, NO, is attracting widespread interest, from environmental to biological chemistry. 1,2 As a free radical, NO reacts rapidly with other odd-electron species, such as superoxide and alkyl radicals, and reversibly dimerizes to N 2 O 2 . NO can be oxidized to NO + or to NO 2 -(by formal addition of O •-). Reduction of NO to N 2 O commonly occurs via deoxygenation of N 2 O 2 , often in a metal-mediated process. 3 Reported here is the first example of reduction of NO to N 2 O that occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Recently, it was shown that the labile azoxymetallacyclopentene complex can be trapped by reactions with MeO 3 SCF 3 (alkylation of the b-N-atom). 96,97 It is interesting to note that the reverse reaction, the formation of N 2 O from a metal nitride complex and nitric oxide, has been observed for an osmium 101 and a ruthenium 49 nitride complex. In case of Ti, the initial N 2 O adduct is more stable and can be used for further reactions.…”
Section: N 2 O As N-atom Donormentioning
confidence: 99%
“…Recently, it was shown that the labile azoxymetallacyclopentene complex can be trapped by reactions with MeO 3 SCF 3 (alkylation of the b-N-atom). 96,97 It is interesting to note that the reverse reaction, the formation of N 2 O from a metal nitride complex and nitric oxide, has been observed for an osmium 101 and a ruthenium 49 nitride complex. In case of Ti, the initial N 2 O adduct is more stable and can be used for further reactions.…”
Section: N 2 O As N-atom Donormentioning
confidence: 99%
“…In general, Os(VI) nitrido complexes are electrophilic (though organometallic nitrides are nucleophillic) [79] and react with various nucleophiles to form products with new bonds to the nitride nitrogen atom (Scheme 8). [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] The nitrido group in these Os compounds does not display significant nucleophilicity. In fact, Osnitrido species react with electrophilic acylating reagents via ligand substitution pathways that keep the OsN bond intact.…”
Section: Imido Complexes Of the Late Transition Metals 37mentioning
confidence: 99%
“…Osmium(vi) nitride species containing nitrogen-based ligands, such as cis-and trans- [Os VI (N)(tpy)Cl 2 ] + (tpy = 2,2Ј:6Ј,2ЈЈ-terpyridine), [Os VI (N)(tpm)Cl 2 ] + [tpm = tris(1pyrazolyl)methane], [Os VI (N)(Tp)Cl 2 ] [Tp -= hydrotris(1pyrazolyl)borate], and [Os VI (N)(bpy)Cl 3 ] (bpy = 2,2Ј-bi-pyridine), have been shown to exhibit novel electrophilic properties. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] A variety of reagents such as phosphanes, amines, cyanide, azide, Grignard reagents, arylboranes, amine N-oxides, alkenes, and disubstituted benzenethiols have been reported to add to the nitride ligand. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] These reactions are summarised in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%